QOL-03. ADDING A PARENT TO THE BRAIN TUMOR TEAM: EVALUATING A PEER SUPPORT INTERVENTION FOR PARENTS OF CHILDREN WITH BRAIN TUMORS. Issue 2 (22nd June 2018) - Nelson, Mary; Riley, Kathy
Abstract: Due to the physical and neurocognitive challenges that often result, childhood brain tumors present profound challenges to patients and families. To address these challenges, the California Chapter of the Pediatric Brain Tumor Foundation provides hospital-based support to parents of children with brain tumors from a Veteran Parent (VP). This mixed-methods, cross-sectional study was designed to evaluate the effectiveness of this intervention utilizing validated tools to compare parental resilience and impact of illness on the family between parents who met with the VP and those who did not. Additional qualitative data gleaned from focus groups with stakeholders (healthcare providers and parents) was analyzed using key constructs of Social Support theory. Although there were no significant differences in overall scores on the PedsQL™ Family Impact module or CD-RISC © between groups, parents in the intervention group scored better on items related to handling difficult decisions and painful feelings (p ≤ .02). Parents in both the English and the Spanish focus groups most frequently described support they received from the VP in terms of emotional and informational support. The social identity parents shared with the VP from their common life experiences also provided a safe environment for emotional and informational support. Results characterize the impact of peer parent support and elucidate parental need for emotional and instrumental support.